Prevention of venous thromboembolism after total knee replacement by high-dose aspirin or intermittent calf and thigh compression. Issue 6213 (23rd February 1980) - McKenna, R; Galante, J; Bachmann, F; Wallace, D L; Kaushal, P S; Meredith, P
Abstract : A prospective study of patients undergoing total knee replacement was carried out by using a combination of 125I-fibrinogen scanning and phlebography, and showed a high incidence of venous thromboembolic disease (TE). Ventilation-perfusion lung scanning was performed to detect pulmonary emboli in most patients. High doses of aspirin and an intermittent low-pressure pneumatic compression device (IPCD) were effective, even in women, in preventing TE. Low doses of aspirin and placebo were equally ineffective in preventing TE. Lung-scan abnormalities compatible with pulmonary emboli were found in six out of 10 patients with isolated calf-vein thrombi. Conventional tests of platelet function did not predict the development of TE. No significant differences were found between the patients receiving low and high doses of aspirin with respect to the mean template bleeding time or platelet aggregation in response to adenosine diphosphate, collagen, and epinephrine, although these variables were significantly abnormal in the two groups receiving aspirin compared with those treated with placebo and the IPCD. Thus high doses of aspirin and a new low-pressure IPCD were effective in preventing venous TE in patients (predominantly women) undergoing total knee replacement.